A proposal of measures towards a qualitative enhancement of bus transport services in the Primorsko-goranska County - Vilke, Siniša (Array, 2018)
The survey, which consisted of counting, polling and recording, has provided data on the existing volume of passenger flows in public bus stations/terminals within the Primorsko-goranska (Littoral-Mountainous) County (hereinafter: the PG County), the density rate of passengers on bus lines that operate on County connections and on bus lines connecting the PG County with other counties in Croatia. In addition to the quantitative parameters, the qualitative data were analyzed that had been obtained by polling passengers at the Rijeka bus terminal, whereupon detailed opinions of direct users of the service were elaborated with the aim of obtaining a picture of the current situation of the public bus transport in the PG County. The data collected were used in evaluating the quality of the passenger transport service provided and in determining measures to be taken in order to bring both the actual quality of transport and the satisfaction of passengers to a higher level.